Whole body perfusion for hybrid aortic arch repair: evolution of selective regional perfusion with a modified extracorporeal circuit. (April 2017) - Fernandes, Philip; Walsh, Graham; Walsh, Stephanie; O'Neil, Michael; Gelinas, Jill; Chu, Michael W. A.
Background: Patients undergoing hybrid aortic arch reconstruction require careful protection of vital organs. We believe that whole body perfusion with tailored dual circuitry may help to achieve optimal patient outcomes. Methods: Our circuit has evolved from a secondary circuit utilizing a cardioplegia delivery device for lower body perfusion to a dual-oxygenator circuit. This allows individually controlled regional perfusion with ease of switching from secondary to primary circuit for total body flow. The re-design allows for separate flow and temperature regulation with two oxygenators in parallel. All patients underwent a single-stage operation for simultaneous treatment of arch and descending aortic pathology via a sternotomy, using a hybrid frozen elephant trunk technique. Results: We report six consecutive patients undergoing hybrid arch and frozen elephant trunk reconstruction using a dual-oxygenator circuit. Five patients underwent elective surgery and one was emergent. One patient had an acute dissection while three underwent concomitant procedures, including a Ross procedure and two valve-sparing root reconstructions. Three cases were redo sternotomies. The mean pump time was 358 ± 131 min, the aortic cross clamp time 243 ± 135 min, the cardioplegia volume of 33, 208 ml ± 16, 173, cerebral ischemia 0 min, lower body ischemia 76 ± 34 min and the average lower body perfusion time was 142 min. Two patients did not require any donor blood products. The median intensive care unit (ICU) and hospital lengths of stay (LOS) were two days and 10 days, respectively. The average peak serum lactate on CPB was 7.47 mmol/L and, at admission to the ICU, it was 3.37 mmol/L. Renal and respiratory failure developed in the salvage acute type A dissection patient. No other complications occurred in this series. Conclusions: Whole body perfusion as delivered through individually controlled dual-oxygenator circuitry allows maximum flexibility for hybrid aortic arch reconstruction. A modified circuit perfusion strategy may help to limit intra-operative metabolic derangements, providing improved clinical outcomes.